Optimisation of lightweight green wall media for greywater treatment and reuse. (March 2018) - Prodanovic, Veljko; Zhang, Kefeng; Hatt, Belinda; McCarthy, David; Deletic, Ana
Abstract: Green walls are increasingly being considered as a suitable greywater treatment technology. Nevertheless, until now there have been no clear recommendations for the use of effective lightweight media in greywater treating green walls. Previous studies of potentially suitable growing media have suggested that a combination of perlite and coco coir might be the most effective for these novel systems. However, there is no clear understanding of what proportion of perlite and coir should be used and how different mixes would affect greywater treatment. This work tested the hydraulic and pollutant removal performance of six different perlite and coco coir media mixes in an unvegetated column experiment. The results suggested that there is a point between 2:1 and 3:1 ratios of perlite to coir where the infiltration rate significantly increases, as the result of perlite dominance. As the infiltration rate increases, the mix gets less prone to clogging, but this negatively affects pollutant removal performance, with insufficient time for biological processes. We therefore optimised the mix for effective long-term treatment of total suspended solids, total nitrogen, chemical oxygen demand and Escherichia coli . Unfortunately, total phosphorus removal from greywater was limited for all tested mixes. This study also showed that attention should be given to greywater inflow dynamics and expected daily water treatment capacity; e.g. systems with a lower hydraulic loading were able to use greater proportion of coir in the mix achieving greater water treatment performance, while systems with higher hydraulic loadings require faster flowing mixes with lower coir proportion. Highlights: Non-vegetated media study for greywater treatment and reuse. Optimised media mixes for treatment of TSS, total nitrogen, COD and E. coli . Phosphorus removal from greywater was limited in all mixes. Pollutant removal performance drop between 2:1 and 3:1 (4:1) perlite to coir ratios. Practical recommendations on appropriate media mix use.